African swine fever virus: A raised global upsurge and a continuous threaten to pig husbandry. (June 2022) - Ata, Emad Beshir; Li, Zi-Jun; Shi, Chun-Wei; Yang, Gui-Lian; Yang, Wen-Tao; Wang, Chun-Feng
Abstract: African swine fever (ASF) is a severe disease affecting pigs with high economic losses and endemicity in various parts of the world. So, it represents a serious threat to the global food safety. The disease was discovered in sub-Saharan Africa where still endemic, and first case was recorded in Kenya in 1921. It is now found all over the world; in Africa, Europe, Asia, and the Pacific it already affects more than 50 countries including Republic of Korea, China, Malaysia, Germany, Bhutan, and India. The P72 protein encoded by the B646L gene is the major protein that reveals high reactogenicity and antigenicity. While the P54 plays a significant role in virus pathogenesis especially cell apoptosis. Multiple virus proteins can suppress the apoptosis of the infected cell at an early stage. The disease spreads through contact with the diseased cases, contaminated fomites, and tick bites. Meanwhile, contaminated water sources might be an essential source of infection. The recovered animals have a significant role in disease persistence as silent carriers. Multiple factors might lead to the observed disease seasonality. Route of exposure, infectious dose, and herd immunity are the main determinants of disease severity and clinical signs. The several types of PCR are well-accepted standard tests for early diagnosis. Although commercial ELISAs were stipulated by OIE, it should be combined with some other virology inspections or serological assays. The ASFV-free countries should be protected against the virus entrance especially that all developed vaccines failed to provoke enough immunity status against the challenged virus. Moreover, it accelerates the speed of revealing clinical symptoms. Highlights: African swine fever virus is an upsurge threaten to pork industry all over the world. The virus can avoid host immune response and suppress synthesis of some proteins. The multiple routes of infection and transmission increase spreading rates. Role of carriers in virus epidemiology should be reevaluated. Disease entrance' prevention is the main tool of control due to inefficiency of the produced vaccines.